Economic Motivations for Master’s Students’ Choice of Educational, Scientific and Professional Trajectories - Sandler, Daniil Gennadyevich; Sushchenko, Anastasia Dmitrievna (Economy of Regions, 2016)
The article examines the motivations for Masters students’ choice of individual trajectories. In the course of their studies, the students’ trajectories have educational, scientific and professional aspects. Educational, scientific and professional students’ trajectories determine a system of interaction between masters students and other people in the context of educational process (teachers, other students) and beyond it (employers, research workers from Russian and foreign universities). The authors emphasize the importance of studying the masters students’ individual trajectories from both scientific (identifying the peculiarities of students’ trajectories formation and development) and practical points of view (investments to masters students to enhance the professional competence in the regional labour market). The authors have analysed the masters students’ individual trajectories on the basis of monitoring data obtained from the survey carried out in February and December 2014. The masters students’ assessments allowed to identify what educational experience they were able to get during the education and whether their experience met their expectations. The masters students’ economic expectations are examined during the implementation of educational and professional trajectories. The analysis of the results has shown that the biggest gap between the expectations and the experience of the masters students was found according to the criteria related to the students scientific trajectory and opportunities to participate in the internationalisation processes. The results of the research may be used to improve the masters programmes taking into account the revealed masters students’ expectations, as well as to ensure highly qualified professionals in the labour market and for the effective investments to the human capital by the government authorities.